Verb inflection in German-learning children with typical and atypical language acquisition: the impact of subsyllabic frequencies*. Issue 1 (5th December 2012) - OTT, SUSAN; HÖHLE, BARBARA
ABSTRACT: Previous research has shown that high phonotactic frequencies facilitate the production of regularly inflected verbs in English-learning children with specific language impairment (SLI) but not with typical development (TD). We asked whether this finding can be replicated for German, a language with a much more complex inflectional verb paradigm than English. Using an elicitation task, the production of inflected nonce verb forms (3 rd person singular with - t suffix) with either high- or low-frequency subsyllables was tested in sixteen German-learning children with SLI (ages 4;1–5;1), sixteen TD-children matched for chronological age (CA) and fourteen TD-children matched for verbal age (VA) (ages 3;0–3;11). The findings revealed that children with SLI, but not CA- or VA-children, showed differential performance between the two types of verbs, producing more inflectional errors when the verb forms resulted in low-frequency subsyllables than when they resulted in high-frequency subsyllables, replicating the results from English-learning children.